GAUGING THE VERTICAL SPECIALIZATION IN EU TRADE - IULIA MONICA OEHLER-SINCAI (Global Economic Observer)
The purpose of this paper is threefold. First, we review the mechanisms and determinants of vertical specialization (VS), as this has gradually become the dominant characteristic of international trade. Second, we underline that there is a rich literature regarding VS in EU trade, at aggregate and individual levels and research is advancing together with the instruments used to measure trade in value added. Third, our investigation brings to the forefront a classification of EU countries according to their GVC participation index, taking into consideration both upstream and downstream links. As a conclusion, the VS analyses help us better understand the interconnectedness among countries and industries by means of foreign direct investment, trade, labour migration and technology transfer.